LIMITATIONS ON COMPLAINTS IN COHABITATION AND ADULTERY ACCORDING TO THE NATIONAL CRIMINAL CODE - Musawir; Ahmad Syahird; Miftahul Jannah; Erlangga Putra Mulya (PT. Radja Intercontinental Publishing, 2026)
The regulation regarding the crime of cohabitation and adultery in the National Criminal Code is part of the national criminal law reform that seeks to adapt the law to the moral, religious, and cultural values of Indonesian society. This regulation is accompanied by a limitation on complaints through an absolute complaint offense mechanism that only grants the right to complain to certain parties. This study aims to analyze the normative construction of the limitation on complaints in the crime of cohabitation and adultery according to the National Criminal Code and examine its relevance to the objectives of the national criminal law reform, with a statute approach, a conceptual approach, and a philosophical approach. The legal materials used consist of primary legal materials in the form of the National Criminal Code and related regulations, secondary legal materials in the form of books, journals, and opinions of criminal law experts, as well as tertiary legal materials that support the research. The analysis was conducted qualitatively by examining the synchronization of norms and criminal law politics in the regulation of moral offenses. The results of the study indicate that the limitation on complaints in the crime of cohabitation and adultery is a form of criminal law politics that aims to limit state intervention in the private sphere of citizens and prevent excessive criminalization. These regulations reflect a balance between protecting moral values and respecting individual privacy rights. However, the limitations on complaints also raise normative issues related to legal certainty and the effectiveness of protecting moral values in Indonesia's pluralistic society. Therefore, a more adaptive and proportional criminal law policy is needed to ensure that the regulation of criminal acts of cohabitation and adultery continues to reflect the values of justice, expediency, and legal certainty within society.